2002
DOI: 10.1080/13504850210128820
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between human capital accumulation and economic growth

Abstract: The central concern of this article is to give new empirical conclusions on the relationship between human capital and economic growth. With this aim, it runs an estimation that allows us to analyse not only the contribution of human capital to output growth, but also the effect of the level of income on human capital accumulation. In particular, it uses Spanish economic data to jointly estimate the equations of the dynamic system that describes the behaviour of the economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
3
9
0
1
Order By: Relevance
“…In terms of human capital development, the empirical literature reviewed in this study shows that human capital development is positively and significantly associated with economic growth (Fischer 1992;Knight, Loayza, and Villanueva 1993;Easterly and Levine 1997;Chen and Feng 2000;Radelet, Sachs, and Whang-Lee 2001;Freire-Seren 2002;Bayraktar 2006;Anyanwu 2014). However, in some cases human capital development was found to be negatively and significantly associated with economic growth (Hamilton and Monteagudo 1998).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In terms of human capital development, the empirical literature reviewed in this study shows that human capital development is positively and significantly associated with economic growth (Fischer 1992;Knight, Loayza, and Villanueva 1993;Easterly and Levine 1997;Chen and Feng 2000;Radelet, Sachs, and Whang-Lee 2001;Freire-Seren 2002;Bayraktar 2006;Anyanwu 2014). However, in some cases human capital development was found to be negatively and significantly associated with economic growth (Hamilton and Monteagudo 1998).…”
Section: Discussionmentioning
confidence: 81%
“…These include Bleaney, Gemmell, and Kneller (2001), Freire-Seren (2002), Anaman (2004), Acikgoz and Mert (2005), Bayraktar (2006), Asheghian (2009) and Checherita-Westphal and Rother (2012). The methodological approach adopted in these studies was also mixed and included cross-country, panel and single-country regressions.…”
Section: Determinants Of Economic Growth In Developed Countriesmentioning
confidence: 99%
“…Some scholars that research on the relationship between human capital accumulation and economic growth do not take into account the possible reverse impact of growth in human Cheng and Hsu (1997) in a study for Japan found bidirectional causality between human capital and economic growth. More recently Freire-Sere´n (2002) for the case of Spain proposed a new interpretation which assumes that the level of income achieved by the economy determines the accumulation of human capital. These interpretations are in line with the findings of the present study which show a positive correlation between market access and human capital accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Other way draws attention to the contribution of human capital in technology through education since it can help to innovation, adoption, and diffusion of new technologies. In this way, human capital contributes to productivity growth, which is described as 'rate effect' [23].…”
Section: Impact Of Human Capital On Economic Growthmentioning
confidence: 99%